Utilization and Fortification of Patin Fish on Extrusion Snack - Mala Nurilmala; Pipih Suptijah; Yugha Subagja; Taufik Hidayat (Jurnal Pengolahan Hasil Perikanan Indonesia, 2014)
Catfish (Pangasius sp.) is a well cultured freshwater fish. Fortification improves protein level in snack and an effort to vary catfish fish product. The purpose of this study was to determine drying method for fish grit, formulation of snack and its properties. Grit formation by several drying methods and proximate (AOAC) and degree of polarization. Snack used based on the physical measurement, namely development ratio. Formulations of grit composition of corn: rice: fish were 70%:30%:0% (K), 65%:25%:10% (A), 62.5%:22.5%:15% (B), 60%:20%:20% (C). Fish addition only effect the color of snack based on sensory analysis. There was no effect on snacks physical properties both 10% and 15% of fish grit added. Chemical measurements comprised water, ash, lipid, protein levels and polarization degree. Statistical analysis showed that fish addition effect the protein level on extrusion snack. In addition, polarization measurement showed that the snack with fish addition of 10% (A) and 15%( B) are fully gelatinized.Keyword: formulation, patin fish, snack